Seismic Performance of an Earth Dam Strengthened with HDPE Geogrids by Finite Element Analysis (Architecture Image Studies, 2026)
Earth dams constructed in seismic areas are very susceptible to the strong ground shaking, particularly when in near-full reservoir conditions that cause increase of system requirement through hydro-mechanical interaction. The present article studies the dynamic response of Al-Adhaim Dam during El-Centro earthquake record (PGA = 0.30 g) at full reservoir level (EL = 143 m) with and without buttressing from high-density polyethylene (HDPE) geogrid during its service life. A fully coupled flow–deformation finite-element formulation was used for the analysis of the seismic displacement, acceleration amplification, stress redistribution, pore-pressure response, seepage behavior and overall stability. Results show that the unretrofitted dam undergoes large seismic-induced deformations of 0.33 m and peak crest acceleration amplifications up to 0.78 g, which result in a well FOS